A pilot investigation of the volunteer work participation of mental health consumers - Young, Janelle Margaret (Curtin University, 2008)
Mental illness is often associated with social isolation, unemployment and limited community participation. Mental health rehabilitation services aim to decrease these psychosocial effects of illness and encourage better community integration for mental health consumers. Volunteer work is one avenue in which consumers can become actively involved with their local communities. However whilst often supported clinically, limited empirical evidence exists which supports the use of volunteer work as a potential mode of rehabilitation for consumers. The overall aim of this study was to document consumer perceptions and experiences with volunteer work and to identify if participation in volunteer work has a positive impact on their mental health. Phase one of this study involved in-depth interviews with nine consumers currently volunteering. Themes identified from these interviews supported the notion that volunteer work is a meaningful occupation for consumers and one which promotes community integration and supports consumer recovery. Findings from the interviews also guided the development of a volunteer scale for later use within the study. Phase two involved the development and pilot testing of a volunteering questionnaire which measured consumer attitudes and experiences with volunteer work. This scale was combined with other standardised tests which measured the mental health variables of personal empowerment and quality of life. Phase three involved the administration of the questionnaire battery developed in phase two. The battery was distributed and completed by thirty consumers, including both those who were and were not volunteering. Analysis conducted identified that overall consumers held a positive view of volunteer work, believing it was a way of developing work skills, friendships and promoting positive mental health.Analysis comparing the volunteering to the non volunteering group indicated that those volunteering experienced better quality of life, specifically within the psychological health, social relationships and personal environment domains. This provides support for the hypothesis that participation in volunteer work promotes consumer recovery. However, age was identified as a potential confounding variable and so the significant results should be viewed with caution. Cost, stigma and becoming unwell during volunteering were identified as barriers to consumer participation. It is argued that mental health services are in a good position to support consumers not only to access but also to maintain ongoing volunteer participation. To date minimal evidence has existed that supported this intervention. This study has begun to fill this research void, however, small study numbers and the cross-sectional, descriptive design make establishing a cause and effect relationship impossible. It would thus be beneficial to conduct a larger study investigating the impact further, including measuring the influence of any interventions that promote consumer participation in volunteer work, such as supported volunteering.